Jawaharlal Nehru : rebel and statesman - Nanda, B. R. (Bal Ram), 1917-2010. (New Delhi : Oxford University Press, 1998)
Full of fascinating and rare halftones of Nehru, this biography strikes a much-needed balance between the adulation accorded Nehru during his lifetime and the denigration - often quite ill-founded - heaped upon since.
Originally published: 1995.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Keywords: Nehru, Jawaharlal, -- 1889-1964.; Prime ministers -- India -- Biography; India -- History -- 1947-